Attacking performance analysis during 2-minute suspensions in female handball games at the Rio 2016 Olympic Games - Trejo-Silva, A.; Gomez-Ruano, M. A.; Parmar, N.; Brazo-Sayavera, J. (Kinesiology, 2025)
The aim of this study was to analyse the effect of the IHF 2016 rule change on attack efficacy during the different numerical asymmetry scenarios associated with 2-minute suspensions at the Rio 2016 OG. A total of 328 exclusion scenarios that were sanctioned during the 38 matches played at the Rio 2016 OG female handball tournament by 12 national teams were analysed using observational methodology. Chi-square test was applied to identify associations between the variables. Chi-square automatic interaction detection trees (CHAID) were used to identify which attacking performance variables during exclusions were associated with the different types of numerical asymmetry (superiority, inferiority with the goalkeeper at goal and inferiority with the empty net). Results during contexts of superiority showed that scoring in 58.0% of the total attacking finalizations (i.e., attack efficacy) (p<.001; ASR 8.2); playing fast transitions (p<.001; x2 = 17.692) and using a 2:4 (with two pivots) offensive system were predictors of the attacking performance of the teams. Substitution of the goalkeeper for a court player during inferiority context was a predictor for teams ranked 9 to 12 and also for those playing for medals (p<.001; x2=26.590) but conceding, as a consequence of their finalizations, a counterattack (p<.001; x2=112.107). Despite teams showing similar attacking performance during numerical superiority compared to previous studies, findings in this study revealed a tendency for empty goals during numerical inferiority context. Coaches should therefore consider training retreat strategies when playing without a goalkeeper when faced with a numerical disadvantage.